Career Planning for Students at Angkatan Belia Islam, Penang, Malaysia - Heryati , Yati; Soraya, Zalkha; Fattah , Sulaeman; Nasrullah; Sulviani; Ramadhan, Ibnu Shabur (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity focuses on addressing the challenges faced by teenagers in the Angkatan Belia Islam Malaysia (ABIM) Penang branch regarding their lack of understanding and skills in career planning. Teenagers in ABIM encounter several key issues when determining their future careers, primarily the absence of guidance and limited access to career-related information.The program aims to enhance the participants' knowledge of the importance of career planning, help them identify their potential, and develop strategies to achieve their career goals. This activity employs a combination of educational and practical approaches. Education is delivered through interactive seminars covering career planning, professional introductions, and personal skill development. Practical activities include individual consultations, mock job interviews, and workshops on creating a Curriculum Vitae (CV).The results of this activity demonstrate improved participant understanding of career planning concepts, enhanced ability to formulate strategic steps towards their career aspirations, and increased self-confidence. This initiative is expected to have a long-term impact on participants as they navigate the competitive job market. Strengthening partnerships with local organisations is also a crucial element in ensuring the sustainability of this program in the future.